Design and Implementation of a Fire Detection and Extinguishing System Using Dual Axis Mechanics - Hidayat, Sharul; Maria, Putut Son; Hilman Zarory; Ahmad Faizal (Jurnal Sistem Cerdas, 2024)
Fire detection and extinguishing systems play an essential role in anticipating the impact of more severe damage to residential installations, warehouses, and buildings that store valuable goods or important documents. This research develops an automatic fire detection and extinguishing system using the dual-axis rotational principle. The flame channel sensor is used by modifying its default position to be collateral (facing the same plane at the same angle). The dual-axis principle allows panning and tilting movements to yield a broader scope for detecting and extinguishing fires. The Dual Axis built in the research has a panning angle range of 113° and a tilting angle of 45°. The results show good performance with a fire detection accuracy rate of 73-100% and a successful extinguishing rate of 76-96%. The implementation of dual-axis rotational construction in the automatic fire extinguishing system not only improves the detection coverage but also increases the chance ratio of more targeted extinguishing.